Região do espaço que mais influencia em medidas eletromagnéticas no domínio da frequência: caso de uma linha de corrente sobre um semi-espaço condutor - BRITO, Licurgo Peixoto de (Universidade Federal do Pará, 2014)
One of the major interpretation problems in geophysics is to determine the region in the subsurface which generates the main part of the signal. In this thesis, the position and size of this region, hereinafter called the main zone, have been found by modelling an electromagnetic system in which the source is an infinite line of electric current, extended over a conductive half-space. The earth has been modelled as a conductive half-space with an inhomogeneity in it as being an infinite layer or a prism of infinite length in the direction of the source line. The signal in the receiver of an electromagnetic system over a conductive homogeneous half-space is different from the one taken over the half space including an inhomogeneity. This difference is a function of the position of the inhomogeneity in relation to the transmiter-receiver system, besides other parameters. Therefore, with the other parameters fixed, there will be a specific position where this difference will maximize. Since this position depends on conductivity contrast, inhomogeneity dimensions and on source frequency, instead of a single position one will have a region where the inhomogeneity will give the maximum contribution to the measured signal. This region is called the main zone. Once the main zone is identified, the targets in the subsurface can be more precisely located. Usually they are conductive parts of the earth with some specific interest. One can facilitate the exploration and reduce production costs if these conductors are well identified during prospecting. A detectability function (∆) has been defined to measure the contribution to the signal due to the inhomogeneity. The ∆ function has been computed using amplitude and phase of the magnetic field components: Hx and Hz which are, respectively, the tangential and the normal to the earth's surface. The size and position of the main zone has been identified using the extremais of the ∆ function, which change with conductivity contrast, and the inhomogeneities' size and depth. Electromagnetic fields for one-dimensional models were calculated using a hybrid form, numerically solving the integrals that were obtained analytically. Two-dimensional models were computed numerically, by the finite elements technique. The maximum values of ∆ function, computed with amplitude of Hx, have been chosen to locate the main zone. This shows more stable results than other amplitude and phase components, both for one and two-dimensional models, when physical properties and geometric dimensions are changed. For the one-dimensional model, where the inhomogeneity is an infinitely extended horizontal layer, the depth of its central plane was found to be po = 0.17 δo, where po is the depth of this central plane and δo is the skin depth for the plane wave (in an homogeneous half-space having a conductivity σ1 equal to that of the backgound, and the frequency w corresponding to the maximum value of ∆ calculatede for the amplitude of Hx). For two-dimensional inhomogeneities, the co-ordinates of the main zone central axis was found to be do = 0,77 r0 (where do is the horizontal distance from this axis to the source) and po = 0,36 δo (where po is the depth of this central axis), with r0 being the source-receiver separation and δo the skin depth in the same conditions as in the one-dimensional case. If the values of r0 and δo are known, it is possible to determine (do, po). Associating each value of ∆ function (calculated using the amplitude of Hx) with the values of d = 0,77 r and p = 0,36 δ for each r and w used to generate ∆, a method to locate the main zone is sugested. The isovalue curves of ∆ are plotted to construct sections of ∆. These sections indicate the conductors position and provide some helpful insight into their geometric forms when the values of ∆ get dose to the maximum.